Exploring Gender Inclusivity in Primary Schools through School Culture and Classroom Practices in Rural Areas of Bangladesh - Nawrin Sultana; Md. Fajlay Rabbi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Gender inclusivity in primary education has become a central concern in efforts to ensure equitable schooling, yet the gap between policy and classroom reality remains wide in rural South Asia. This study examines how school culture and classroom practices shape the gender experiences of children in rural primary schools in Lalmonirhat district, North-Bengal, Bangladesh. The research draws on qualitative data from direct classroom observations in ten government primary schools, semi-structured interviews with fifty teachers and ten headteachers, focus group discussions with one hundred students and fifty parents, and review of school documents. To complement the qualitative findings, the study also reports descriptive indicators on questioning frequency, disciplinary incidents, attendance, and infrastructure across the ten schools. Findings show that despite national policies on inclusive education, gender stereotypes shape teacher expectations, disciplinary practices, and classroom attention in ways that disadvantage both girls and boys. Girls face barriers tied to patriarchal household norms, poor sanitation, early marriage pressures, and a culture of silence that limits their participation. Boys face punitive discipline, economic marginalisation, and rigid masculine norms that constrain their engagement with literacy and the arts. The study argues that Gender Responsive Pedagogy, targeted teacher training using case-based and role-play modules, gender-sensitive behaviour management, and community engagement form a connected set of interventions that can address these barriers. School-related gender-based violence emerges as an urgent concern requiring policy attention. The findings support a shift from enrolment-centred metrics of gender equality towards measures of participation, wellbeing, and learning achievement.